TEACHERS’ CHALLENGES IN TEACHING ENGLISH AT SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 18 JAMBI - husna, Faradilla Husna; Edi Rozal; Reni Andriani (JR-ELT (Journal of Research in English Language Teaching), 2021)
The purpose of this research is to determine the difficulties that English instructors face when working with pupils in the seventh grade at Junior High School 18 in Jambi. A qualitative descriptive method was utilized throughout the course of this research. For the purpose of gathering data for this investigation, the researchers utilized observation sheets as well as interview sheets. Based on the findings of the data collection, the researchers discovered that there are various obstacles for teachers to overcome when teaching English to students in the seventh grade at Junior High School 18 Jambi. Dealing with kids, the amenities in schools, and even other teachers can provide a number of difficulties. The challenges include a lack of student interest in learning English, a lack of basic knowledge of students about English lessons, the use of a student's mother tongue when learning English, facilities at school, teacher unfamiliarity in technology, and insufficient time lesson hours due to the Covid-19 pandemic that is happening right now.